2021
DOI: 10.1038/s41598-021-00601-2
|View full text |Cite
|
Sign up to set email alerts
|

Synbiotic (Lactiplantibacillus pentosus GSSK2 and isomalto-oligosaccharides) supplementation modulates pathophysiology and gut dysbiosis in experimental metabolic syndrome

Abstract: Metabolic syndrome a lifestyle disease, where diet and gut microbiota play a prodigious role in its initiation and progression. Prophylactic bio-interventions employing probiotics and prebiotics offer an alternate nutritional approach towards attenuating its progression. The present study aimed to evaluate the protective efficacy of a novel synbiotic (Lactiplantibacillus pentosus GSSK2 + isomalto-oligosaccharides) in comparison to orlistat in an experimental model of metabolic syndrome. It was observed that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
3
4
0
Order By: Relevance
“…Modulation of fatty acid oxidation in HFDinduced metabolic diseases (obesity, T2DM) may be attributed to a reconstruction of gut microbiota composition, via regulating secretion of gut hormone glucagon-like peptide-1 (belonging to incretin system, responding to food intake by promoting insulin secretion). 62,63 Disturbance of gut microbiota composition, such as the increased F/B ratio and decreased gut Lactobacillus abundance, could induce metabolic syndrome, 64 which was observed in this work as well. TSs administration altered intestinal microbiota dysbiosis, resulting in the enhancement of fatty acid oxidation, which was manifested by increased palmitoylcarnitine content.…”
Section: Discussionsupporting
confidence: 64%
“…Modulation of fatty acid oxidation in HFDinduced metabolic diseases (obesity, T2DM) may be attributed to a reconstruction of gut microbiota composition, via regulating secretion of gut hormone glucagon-like peptide-1 (belonging to incretin system, responding to food intake by promoting insulin secretion). 62,63 Disturbance of gut microbiota composition, such as the increased F/B ratio and decreased gut Lactobacillus abundance, could induce metabolic syndrome, 64 which was observed in this work as well. TSs administration altered intestinal microbiota dysbiosis, resulting in the enhancement of fatty acid oxidation, which was manifested by increased palmitoylcarnitine content.…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, it has been shown that probiotic intervention in HFD-fed rats resulted in reduced serum ALT and AST levels, as well as reduced expression of the pro-inflammatory markers TNF-α and IL-6. 27 Numerous studies have shown that probiotics improve the clinical outcome of HFD patients by influencing host gut microbiota. As a result, we performed a shotgun metagenomic role in regulating the immunity and metabolism of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been shown that probiotic intervention in HFD-fed rats resulted in reduced serum ALT and AST levels, as well as reduced expression of the pro-inflammatory markers TNF-α and IL-6. 27…”
Section: Discussionmentioning
confidence: 99%
“…Further, dysbiosis itself can increase the intestinal CD36 receptor expression and induce lipogenesis through long‐chain fatty acids (LCFAs) absorption, directly linked to abnormal circulatory metabolites, metabolic endotoxemia, and low‐grade systemic inflammation (Figure 2). 114,120,121 To boost gut immunity and manage inflammatory diseases, different probiotic, prebiotic, and synbiotic supplements are currently being used and these have significant benefits for MetS 122,123 . Thus, modulation of diets, probiotics, prebiotics, synbiotics, alternative medicine, and exercise may restore the tissue microenvironment in the stomach, particularly by restoring epithelial integrity and mucosal immunity, which may slow down tissue inflammation, ultimately improving MetS.…”
Section: Pathophysiology Of Metsmentioning
confidence: 99%
“…114,120,121 To boost gut immunity and manage inflammatory diseases, different probiotic, prebiotic, and synbiotic supplements are currently being used and these have significant benefits for MetS. 122,123 Thus, modulation of diets, probiotics, prebiotics, synbiotics, alternative medicine, and exercise may restore the tissue microenvironment in the stomach, particularly by restoring epithelial integrity and mucosal immunity, which may slow down tissue inflammation, ultimately improving MetS.…”
Section: Chronic Inflammationmentioning
confidence: 99%